2021
DOI: 10.30998/scope.v5i2.8544
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Indonesian EFL Argumentative Writing Using Toulmin’s Model: The Structure and Struggles from the Learners

Abstract: <p>Argumentative writing plays an important role in academic writing at university level. However, learners mostly find that writing this essay a challenging and effortful task. This present study aims at exploring the structures of argumentative essay written by Indonesian EFL students from one university in Jakarta Indonesia. Moreover, it investigates their difficulty and constraints during composing the essay. Using a descriptive qualitative design, the authors selected writing assignment and question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…In the last few decades, a number of studies have analyzed the structure of argumentative writing by using Toulmin's theoretical framework (Toulmin, 1958(Toulmin, , 2003Lea and Street, 1998;Németh and Kormos, 2001;Qin and Karabacak, 2010;Wolfe, 2011;Rapanta et al, 2013;Abdollahzadeh et al, 2017;Sundari and Febriyanti, 2021). The model proposed by British Philosopher Toulmin (1958) has been used to analyze the argumentative writing (Figure 1).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few decades, a number of studies have analyzed the structure of argumentative writing by using Toulmin's theoretical framework (Toulmin, 1958(Toulmin, , 2003Lea and Street, 1998;Németh and Kormos, 2001;Qin and Karabacak, 2010;Wolfe, 2011;Rapanta et al, 2013;Abdollahzadeh et al, 2017;Sundari and Febriyanti, 2021). The model proposed by British Philosopher Toulmin (1958) has been used to analyze the argumentative writing (Figure 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Nesi and Gardner (2006) put it, the ability to display critical thinking and develop an argument is commonly pursued across academic texts of different disciplines. However, despite the importance of argumentative essay writing in the academic context, there are many studies in both L1/L2 writing contexts which demonstrate the difficulties the students have with argumentative writing (Qin and Karabacak, 2010;Abdollahzadeh et al, 2017;Altınmakas and Bayyurt, 2019;Saprina et al, 2020;Divsar and Amirsoleimani, 2021;Sundari and Febriyanti, 2021). One of the major struggles the students have is with the concept of argumentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means they could conduct claim and warrant, but not with backing or rebuttal (Setiawati & Nurlaelah, 2017). Meanwhile, a more recent study result, which involved students of an academic writing course as the sample, suggested that more practice should be given to the students to improve their argumentation skills (Sundari & Febriyanti, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it is the one with a clear claim backed up by relevant and sufficient data as well as counterarguments challenged by effective rebuttals ( Qin, 2020 ). In other words, a good argumentative writing integrates both the surface structure (i.e., essential elements including claims, counterclaims, rebuttals, and their accompanied data) and the substance (i.e., the quality of reasoning) ( Ho, 2011 ; Uysal, 2012 ; Stapleton and Wu, 2015 ; Qin, 2020 ; Siregar et al, 2021 ; Sundari and Febriyanti, 2021 ; Zhang et al, 2021 ). As an essential marker of critical thinking and a significant feature of argumentative writing ( Wolfe, 2011 ; Hirvela, 2017 ), quality of argument has been measured with an increasing use of the Toulmin model that has gained broad acknowledgment in accounting for the various elements marking the progress of an argument ( Qin, 2020 ) and has been widely used to assess the quality of argumentative writing ( Yeh, 1998 ; Qin and Karabacak, 2010 ; Liu and Stapleton, 2014 ; Stapleton and Wu, 2015 ; Qin, 2020 ; Zhang and Zhang, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%